An observational study of personal and environmental factors associated with attendance at a community-based adaptive fitness center for adults with physical disabilities. Issue 4 (October 2022) - Morgan, Kerri A.; Heeb, Rachel; Flynn, Ashley; Sukow, Kayleigh; Tormey, Erin; Tucker, Susan; Walker, Kim; Hollingsworth, Holly
Abstract: Background: Regular exercise has many benefits for adults with physical disabilities (AwPD). Despite these benefits, significant barriers to participating in exercise exist for AwPD. Community-based adaptive fitness centers promote exercise for AwPD by minimizing barriers. Research has yet to clearly examine the personal and environmental factors associated with enrollment and attendance rates of AwPD in community-based adaptive fitness centers. Objective: The purpose of our study was to explore personal and environmental factors associated with AwPD and their attendance at a community-based adaptive fitness center once enrolled. Methods: Individuals aged 18–85 with a physical disability interested in exercising were referred to a community-based adaptive fitness center. At initial assessment, participants completed demographics, health, barriers to exercise, and exercise self-efficacy (ESE) surveys. Following initial assessment, participant visits to the fitness center were tracked for six months. Results: Of 106 participants, 27 never visited the facility after initial assessment, and the remaining participants with six months of attendance data (n = 67) averaged 14.9 (SD = 14.2) visits. Correlation results showed a negative curvilinear relationship between number of visits and years living with disability (rs  = −0.24, p < 0.05), with higher attendance associated with more recent diagnosis. Logistic and stepwise regressions showed that ESE score (β = 0.107, p = 0.026) was the only significant predictor of attending the fitness center once enrolled. Conclusions: This study demonstrates the importance of understanding personal and environmental factors and assessing ESE for AwPD who are newly enrolled in a community-based adaptive fitness center.